Analysis of In Vitro Cyto- and Genotoxicity of Barbatimão Extract on Human Keratinocytes and Fibroblasts. (8th October 2018) - Pellenz, Neida L.; Barbisan, Fernanda; Azzolin, Veronica F.; Duarte, Thiago; Bolignon, Aline; Mastella, Moisés H.; Teixeira, Cibele F.; Ribeiro, Euler E.; Cruz, Ivana B. Mânica da; Duarte, Marta M. M. F.
Abstract : Barbatimão ( Stryphnodendron adstringens, Mart.) is a native Brazilian species used in traditional medicine and some commercial preparations owing to its strong wound-healing activity. However, controversy regarding its use due to safety concerns over the potential genotoxic effect of this plant remains. In order to clarify this issue, the effect of hydroalcoholic extract of barbatimão in vitro on cell viability, DNA damage, and induction of apoptosis in two commercial cell lines of keratinocytes (HaCaT) and fibroblasts (HFF-1) was evaluated. Barbatimão stem bark hydroalcoholic extract (70% ethanol) was obtained and lyophilized for subsequent use in all experiments. The main bioactive molecules quantified by HPLC were gallic acid, caffeic acid, quercetin, catechin, and epigallocatechin gallate (EGCG). Barbatimão (0.024 to 1.99 mg/mL) was found to decrease cellular mortality as compared to the control group. GEMO assay, a noncellular DNA protocol that uses H2 O2 -exposed calf thymus DNA, revealed not only a genotoxic effect of barbatimão, but also a potential genoprotective action against H2 O2 -triggered DNA fragmentation. These results indicated that barbatimão at concentrations of 0.49 and 0.99 mg/mL, which are near to the levels found in commercial preparations, exerted an in vitro genoprotective effect on cells by decreasing the levels of DNA oxidation quantified by 8-hydroxy-2′-deoxyguanosine (8-OHdG) and reactive oxygen species (ROS) levels. Gene and protein apoptotic markers, quantified by qRT-PCR ( BAX/Bcl-2 genes) and immunoassays (Caspases 3 and 8), respectively, also indicated a decrease in apoptotic events in comparison with control cells. Collectively, the results suggest that barbatimão could exert genoprotective and antiapoptotic effects on human keratinocytes and fibroblasts.